Understanding the spatial distribution of arsenic, cadmium, and mercury concentrations in Blue Mussels (Mytilus edulis) from Skutulsfjörður and Álftafjörður in the Westfjords of Iceland - Hixson, Anna Nicole, 1993- (2019)
Trace elements above natural background levels can be a threat to marine ecosystem health and potentially also human health. Long-term global monitoring programs have generated large datasets that allow for a better understanding of how concentrations of trace elements in the marine biosphere change over time. These monitoring programs utilize water, sediment, and/or biota samples to understand how these elements are interacting in the environment. However, these monitoring programs normally do not investigate oddities or unusual conditions further. In the case of the Westfjords Iceland, concentrations of arsenic (As), cadmium (Cd), and mercury (Hg), have been prominent in the local blue mussel (Mytilus edulis) for over a decade (1999-2018) in Skutulsfjörður and Álftafjörður. Although, these concentrations have shown peculiarities when compared to other monitoring sites in Iceland, they have not been extensively studied. This thesis aimed to generate a better understanding of the distribution of As, Cd, and Hg in Skutulsfjörður and Álftafjörður, highlight potential sources of these pollutants, and establish viable strategies for future research and management. This study reveals that high As is not limited to a single site in Skutulsfjörður (24.05-83.87 mg/kg dw); illustrates the relatively constant levels of all elements in Álftafjörður since its last sampling in 2013; the potential role of pollution sources on these concentrations; and the differences in these concentrations between populated fjords and rural fjords. These findings suggest the need for new management strategies including further monitoring and more widespread analysis of trace elements in biota in this area, to better understand and mitigate any potential negative consequences that these elevated concentrations may have on the surrounding coastal environment. Ólífræn snefilefni yfir náttúrulegum bakgrunnsgildum geta verið ógn fyrir vistkerfi sjávar og hugsanlega einnig fyrir heilsu manna. Langtíma alþjóðleg vöktunarverkefni hafa leitt af sér ...